Taxing high-income earners: Tax avoidance and mobility - Alejandro Esteller; Amedeo Piolatto; Matthew D. Rablen (Institute for Fiscal Studies (IFS), 2016)
The taxation of high-income earners is of importance to every country and is the subject of a considerable amount of recent academic research. Such high-income earners contribute substantial amounts of tax and generate signifi cant positive spillovers, but are also highly mobile: a 1% increase in the top marginal income tax rate increases out-migrations by around 1.5 to 3%. We review research into taxation of high-income earners to provide a synthesis of existing theoretical and empirical understanding. We o ffer various avenues for potential future theoretical and empirical research.
Keywords: H26; H31; K34; K42; 330; high-income earners; mobility; tax avoidance